1994
DOI: 10.1017/s0305004100072170
|View full text |Cite
|
Sign up to set email alerts
|

The class semigroup of orders in number fields

Abstract: Let R be a commutative domain, and let us denote by (R) the set of non-zero fractional ideals of R, which is a commutative semigroup under multiplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 2 publications
(2 reference statements)
0
32
0
Order By: Relevance
“…Bazzoni and Salce in [1] study ideal class semigroups of valuation domains and later Bazzoni in [2] studies the structure of ideal class semigroups of Prüfer domains. Ideal class semigroups of orders in number fields are investigated by Zanardo and Zannier in [21].…”
Section: Note That S(r) Is a Commutative Semigroup With Identity [R]mentioning
confidence: 99%
See 1 more Smart Citation
“…Bazzoni and Salce in [1] study ideal class semigroups of valuation domains and later Bazzoni in [2] studies the structure of ideal class semigroups of Prüfer domains. Ideal class semigroups of orders in number fields are investigated by Zanardo and Zannier in [21].…”
Section: Note That S(r) Is a Commutative Semigroup With Identity [R]mentioning
confidence: 99%
“…G [L] Clifford regular domains are introduced by Zanardo and Zannier in [21] and Bazzoni and Salce in [1]. Bazzoni in [3] is the first to write down the definition of Clifford regular domains and study them in greater detail.…”
Section: Note That S(r) Is a Commutative Semigroup With Identity [R]mentioning
confidence: 99%
“…There is only one maximal ideal lying over P in R if p is ramified or inert. By [12,Proposition 12], we have P = pZ + nωZ when p|n.…”
Section: The Quadratic Casementioning
confidence: 99%
“…Zanardo and Zannier proved that all orders in quadratic fields are Clifford regular domains [20] while Bazzoni and Salce showed that all valuation domains are Clifford regular [5]. The study of Clifford regular domains was then carried on by S. Bazzoni [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%